Chemical looping combustion-adsorption of HCl-containing syngas using alkaline-earth coated iron ore composites for simultaneous purification and combustion enhancement - Liu, Guicai (2022)
For high temperature purification of HCl-containing syngas, chemical looping combustion-adsorption (CLCA) was developed using Ba-, Sr- and Ca-coated iron ore (IO) as bifunctional oxygen carrier-HCl sorbent (OCS) composites. The behavior of OCS at fuel reaction (FR), air reaction (AR) and sorbent regeneration (SR) stages was studied. It was found that compared with conventional chemical looping combustion (CLC), CLCA could maintain high dechlorination performance at FR stage, without any deterioration after multiple cycles. Among the OCS composites, Ba and Sr-coated IO showed extraordinary performance as OCS for CLCA process of HCl-containing syngas, whereas Ca-coated IO exhibited low HCl removal ability. During 5-cycle test of Ba and Sr-coated IO, the HCl concentration in flue gas from fuel reactor was 20–30 ppmv, corresponding to approx. 95% dechlorination efficiency. For the selection of SR conditions, high temperature (950 °C) was required to achieve stable and high regeneration performance, while H2O was the effective regenerating gas for Ba-coated IO, instead of CO2. Regarding syngas combustibility, the coating with alkaline-earth metal compounds improved the oxidizing ability of IO leading to higher combustion efficiency compared to pure IO. Ba- and Sr-coated IO showed greater performance in syngas combustion than Ca-coated IO due to the greater electron donating ability and base strength. The addition of SR stage was also found to promote the syngas combustion performance, due to the mitigation of sintering problem from molten metal chlorides. The results suggest that the CLCA process could be an efficient solution for processing HCl-containing syngas.